Chartering Territories in Outer Space: Obligating the Need for a National Legal Framework in India. Issue 1 (27th April 2018) - Gupta, Biswanath; KD, Raju
ABSTRACT: Space research is heralded as the harbinger of the next level of advancement in science and technology. The fact that countries are spending millions of dollars in this regard is testament to its potential. India is making inroads in the field and, in the last 15 years, has established itself as a dominant player. According to Antrix, the commercial wing of the Indian Space Research Organization, India commercially launched 209 foreign satellites of other countries into space. Apart from this, Antrix is applying its success in other commercial activities, like remote sensing, selling of space objects (parts of satellites and launching vehicles), and mission support. In keeping with this development, the Indian legal position and policy framework with respect to commercial space activities are reviewed. The article also surveys India's commitment to international space law and its reflection in national legislation. Finally, the existing policy related to commercial space in India is examined and measures are suggested to create national legislation for the country to deal with issues of commercial space activities.